Health risk assessment of brachytherapy service engineers at the selected nuclear medicine centres / Muhammad Azfar Rosli - Muhammad Azfar , Rosli (2018)
Brachytherapy is gaining popularity of method to treat cancers. Moreover, a number of studies have been published on brachytherapy. However, not much research are focusing on the radiation worker on maintain the Treatment Unit (TU) which using Iridium-192 isotope with a half-life of 73.83 days. As the technology grow, from manual afterloading into remote afterloading, better safety feature and procedures introduced. What is the safety and health status of a service engineer from the technology and facility improvement? Therefore, the study was done to identify and assess the health risk of engineers from maintenance activity of TU and to study the perceptions of the engineer towards the existing safety in selected nuclear medicine centres. Apart from that, the study aim is to recommend risk control for best measures on safety and protection against unwanted exposure. This research use the method of data collections which is quantitative and qualitative methodologies. In qualitative method, interview and observation at selected oncology department were used during planned maintenance and servicing. In quantitative data, questionnaire were given to the service engineers. Risk calculation were calculated using risk matrix. The study successfully assess and identify the health risk of the service engineers and recommendation had been given to improve the safety of the service engineer during PPM activity. The study also include the perception of the engineers toward the safety feature of the selected hospitals. The study also identified that both low and high risk have the same percentage which is 31% meanwhile medium risk is 38%. The hazards identified consist of 11 physical hazards, 1 biological hazard, 3 ergonomic hazards, and 1 electrical hazard. Based on the risk assessment result, it is also found that tasks posed with high risk value are during exchange source with dummy cable and source check position. There were no injury nor fatality and also nor genetic mutation effect recorded in the study even the activity is involving high risk hazards. Keywords: brachytherapy, service, engineer, safety, Iridium-192